TRANSFORMASI DIGITAL DALAM MENINGKATKAN KESIAPAN KERJA LULUSAN PROGRAM STUDI PENDIDIKAN TEKNIK MESIN UNIVERSITAS PALANGKA RAYA - Yulando, Steven; Suryanto, Ahmad Eko; Supatra, I Made; Supriyadi, Supriyadi (Program Studi Pendidikan Teknik Mesin, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Palangka Raya, 2024)
Digitalization is a major transformation in education, particularly in preparing graduates to face the challenges of the Fourth Industrial Revolution and Society 5.0. This study aims to analyze the impact of digital transformation on the work readiness of graduates from the Mechanical Engineering Education Program at Universitas Palangka Raya. Using a literature review method, the study identifies strategies for integrating technology into the curriculum, developing digital literacy, and collaborating with industries to ensure the relevance of graduate competencies. The findings indicate that technology-based curricula, improved digital literacy among educators, and support for educational infrastructure are critical factors in producing competent and adaptable graduates for the global job market. Strategic recommendations include strengthening professional training to enhance digital competencies among educators, integrating digital literacy into the curriculum, and developing digital leadership at the institutional level. Additionally, collaboration among universities, government, and industries is essential to design policies that support sustainable digital transformation. This study provides significant contributions to higher education institutions in designing strategies to improve graduate work readiness in the digital era